FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS HARIAN TAHUN 2016 - Idaria Sidabukke; Dewi Bancin; Ernawati Barus; Rinny Anggrainy (Jurnal Reproductive Health, 2017)
Children who experience less nutrition and malnutrition will impact seriously against future generations, children who suffer from nutritional deficiency will have physical growth and impaired mental development. Nutritional causes less not only due to the lack of food but also because of infectious diseases. Children who get good food but because the sore often diarrhea or fever can suffer from diseases less nutrition. This research aims to know the factors associated with childhood nutritional Status in the region Harian Dolok Sub Health Center Sigompulon 2016. This type of research is survey design the research design with a cross secsional. The population in this research is all the toddlers who visit clinics in Harian from January to March 2016-2016 as much as 2369 toddlers. The sample contained as many as 71 people are toddlers. Data analysis using univariate analysis, bivariat and multivariate. The results showed that there is a relationship between the knowledge of mothers withtoddlers nutritional status (p = 0,009), there is no relationship to economic status with toddler nutritional status (p = 0.107), there is a relation of exclusive breast feeding with toddler nutritional status (p =<0.001), there is no relationship of completeness of immunization with toddler nutritional status (p = 0,821), there is a relationship between disease companion with the nutritional status of children (p =<0.001), there is a connection with the feeding patterns of nutritional toddler status (p = <0.001) , The most dominant variables related to nutritional status is a pattern toddler feeding (p = <0.001; OR = 6.995% CI 2,806-22,805) means that the feeding patterns of less risky opportunities either have 6.9 timeslarger toddlers experiencing less nutrition than a good feeding pattern. Thus to the mother of a toddler so you can pay attention to childhood eating patterns, as well as data give breast milk to infants from the age of 0-6 months so that the toddler suffered no less nutritional status